Observations about reproduction on captivity of Crocodylus acutus (Cuvier, 1807) in Peru - Pérez, Oswaldo (2005)
Observations about reproduction of Crocodylus acutus (Cuvier, 1807) were recorded during the years 2001 and 2002 in the Fishery Center «La Tuna Carranza» (Puerto Pizarro, Tumbes, Peru). The minimum size of a female nesting was 2,30 m. The percentage of viability and birthrate/natality were 61,71% and 93,15%, respectively.